On the siwaliks observed along some routes in central Nepal (Journal of Nepal Geological Society, 1982)
The Siwaliks of central Nepal were surveyed along six routes. The large part of the Siwaliks in the present area expect for the Upper Siwaliks in the eastern part seems likely to correspond to the Lower to Middle Siwaliks on the basis of their lithology. The western part can be regraded as an upheaved area bounded by Chitawan Dun on the east and by the Rapti and Dang Duns on the west.